The Migration Turn and Eastern Europe: De-homogenising the abstract category of “migrant”: Melegh, A. (2023). The Migration Turn and Eastern Europe: A Global Historical Sociological Analysis. Palgrave Macmillan - Escobedo, Luis (Intersections. East European Journal of Society and Politics, 2024)
In this book review, I employ Attila Melegh’s The Migration Turn and Eastern Europe to retell my own experience, ‘on the ground,’ as someone ascribed the abstract category of ‘migrant.’ I apply the ideas proposed by this book to illustrate how the ‘migration turn,’ as understood here, has restructured my life and experience, while at the same time, although only to a certain extent, de-homogenise said category.